STUDENTS’ PERCEPTION IN LEARNING ENGLISH THROUGH QUIZ FEATURE ON INSTAGRAM STORIES FOR EFL STUDENTS - Fonnalita; Syaprizal; Ani Fiani (Universitas Negeri Surabaya, 2022)
This research aimed to discover the students’ perception of learning English through the Quiz feature on Instagram Stories for EFL students. The method used in this research was a descriptive qualitative approach. Participants of this research were the eleventh-grade students of SMA Negeri 5 Lubuklinggau, and the subject of this research was 35 students of XI MIPA 3 of SMA Negeri 5 Lubuklinggau. Data collection techniques used were the questionnaire and interview results. Data analysis techniques used were basic statistical techniques of percentages using the Likert-scale questionnaire, and the data was supported from the interview’s results as the secondary data. The results of this research showed that the EFL Students have a good perception of learning English through Quiz feature on Instagram Stories. In conclusion, learning English through Quiz feature on Instagram stories for EFL students is good, and this Quiz feature on Instagram stories can be considered as English learning and practice media, which will be better to combine with the conventional ways in the classroom.